The Incompatibility of the European Union Deforestation Regulation with Trade Liberalization - Anthonio Bimo Raditya; Lewiandy (Ekasakti Journal of Law and Justice, 2026)
The European Union Deforestation Regulation (EUDR) is an environmental policy aimed at ensuring that agricultural and forestry commodities entering the European market are free from deforestation practices. While designed to support global sustainability, its implementation poses significant challenges for developing countries, particularly Indonesia, which heavily relies on exports of commodities such as palm oil, rubber, coffee, and cocoa. This study aims to analyze the implications of EUDR on international trade relations and its compatibility with the fundamental principles of the World Trade Organization (WTO), including most-favoured nation, national treatment, and trade liberalization. Using a qualitative normative approach, this research examines relevant legal frameworks, policy documents, and secondary data. The findings indicate that EUDR imposes complex administrative requirements, such as geolocation verification, supply chain traceability, and comprehensive due diligence, which disproportionately burden smallholders and medium-scale enterprises. Furthermore, the regulation potentially reflects elements of green protectionism, creating trade distortions and reducing the competitiveness of Indonesian commodities in the global market. In conclusion, while EUDR promotes environmental sustainability, it may conflict with fair trade principles and hinder market access for developing countries. Therefore, it is recommended that policymakers strengthen domestic readiness, enhance support for smallholders, and pursue diplomatic engagement to ensure fair and balanced trade practices.